Literature Study of Riba In Banking - Harahap, Haddad" Ulum; Harahap, Rijal Allamah (International Journal of Economics and Management, 2023)
The purpose of this article is to understand the history of banks usury and banks usury. From the results of the literature conducted, it seems that there are three opinions on the question of whether a bank's interest is usury. Second, it accepts interest because it is not equivalent to the usury prohibited by Islamic law. Third, bank interest is haram, but it is acceptable because there is no way around it. Muslim scholars and scholars still disagree on the following bank interest laws: Abu Zafra, Abu Ala Al Maudi Abdullah Al Arabi, and Yusuf Kardawa said that interest on traditional banks is included in the nasty Nassia class banned by Islam. Ulama's fatwa on the ban on bank interest was actually established at the Islamic Research Conference, attended by 150 prominent scholars, at the second conference in Cairo, Egypt, in May 1965. Since then, various international and domestic ulama forums have issued fatwas banning bank interest.